Surface Monitoring of the Grasberg Open Pit Mine Using Sentinel-1A Data - Tiara Putri Elizet; Pakhrur Razi; Suci Rizki (GeoREST, 2026)
The Grasberg Open Pit Mine, operated by PT Freeport Indonesia, experiences significant and dynamic ground displacement driven by ongoing, intensive surface and subsurface mining operations. To effectively monitor these complex structural shifts, this study employs Sentinel-1A Synthetic Aperture Radar (SAR) satellite imagery in conjunction with the Interferometric SAR (InSAR) technique to quantify surface deformation with high millimeter-level accuracy across the mining complex. The comprehensive data processing workflow involved multi-temporal C-band Sentinel-1A acquisition, precise interferogram formation, coherence estimation, phase unwrapping, and phase-to-displacement conversion to systematically map line-of-sight (LOS) movements. The empirical results revealed localized land subsidence reaching up to approximately 25 mm, alongside localized surface uplift reaching up to 15 mm over selected observation periods throughout 2025. Furthermore, these spatial deformation patterns highlight the critical influence of localized structural geology, hydrology, and steep topographic gradients on overall slope stability. Ultimately, these findings underscore the high reliability, broad coverage, and cost-effectiveness of spaceborne InSAR for continuous, high-resolution surface deformation monitoring. Integrating routine radar satellite telemetry into site management offers essential early-warning insights for pit slope hazard management, significantly mitigating landslide risks and supporting safer mining practices.